Penguatan Kapasitas Aparatur Desa Bojong Menteng (Lebak) dalam Membangun Desa tanpa Kemiskinan melalui Komunikasi Efektif - Syaifuddin, Syaifuddin; Pandjaitan, Rosmawaty Hilderiah (Universitas Pahlawan Tuanku Tambusai, 2025)
Rural poverty remains a major issue affecting community well-being, particularly in areas like Bojong Menteng, Banten. Village officials play a crucial role in designing and implementing empowerment programs to address poverty. However, numerous challenges remain, including limited capacity for effective communication between village officials and the community. Ineffective communication can hinder the success of village empowerment programs, therefore, strengthening the communication capacity of village officials is crucial. The targeted outcome of this program is that Bojong Menteng Village officials will have a better understanding of effective communication in managing community empowerment programs. The targeted outcomes are improved communication skills among village officials, the creation of synergy between the village government and the community, and the more effective implementation of village programs to alleviate poverty. This program is also expected to provide a communication model that can be applied by other villages facing similar challenges.